PSYCHOLOGICAL-PEDAGOGICAL TRAINING ASPECTS FOR NON-SWIMMERS - Dragan Krivokapić; Olivera Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
In developed countries chronological age from 65 is often mentioned as age limit when elderly age begins, and which is featured by significant changes in organic functions as well as social relations. Thanks to qualitative medical care and contemporary ways of treatment, an average lifetime has been prolonged. Therefore, according to some data in developed countries of Western Europe, each fourth inhabitant is older than 65. However, there psychophysical abilities are very weak, and health is bad, which directly influences reduction in life quality. Adapted physical activities in water adjusted to abilities and health state of elderly people give a series of advantages in comparison to exercises that can be done outside water. For that reason, in those conditions effect of gravity is reduced, so PTO-skeletal system suffers a lot less burden than at practicing on dry. Taking into account that postural system with elderly people is often damaged, great advantage at exercising in water enables horizontal position that a person takes. That beneficially influences first of all the spinal cord, which is in horizontal position disburdened from gravity influence which beneficially affects spinal disease. Results of numerous researches indicate that swimming harmonically burdens organism so that almost all musculature of upper and lower extremities, belly and pelvis area. Swimming accelerates blood circulation, heart gets more blood which directly affects increase in minute volume. Eventually it all brings to fortification of heart muscle and more permanent increase of its functional abilities. Possibility of precise dosing of burden in swimming enables excellent way of therapy with elderly people and those with damaged heart. Besides, activated musculature enables fast relaxation of organism and restore of all vital cardio respiratory functions to the level of standard work ability of a man.